Interactive DICOM image transmission and telediagnosis over the European ATM network. - Neri, E. (IEEE Transactions on information technology in biomedicine)
The European High-Performance Information Infrastructure in Medicine, noB3014 (HIM3) project of the Trans-European Network-Integrated Broadband Communications (TEN-IBC) program, started on March 1996 and finished on February 1997, aimed to test the medical usability of the European asynchronous transfer mode (ATM) network in medical image transmission. The Department of Radiology, University of Pisa, Pisa, Italy, and St-Luc University Hospital, Brussels, Belgium, involved in the project as healthcare partners in the radiological domain, established several connection sessions finalized to test the usability of Digital Imaging and Communication (DICOM) image transmission and interactive telediagnosis tools in the daily radiological practice. The Pisa site was connected to the Italian ATM pilot (Sirius Network) through the Tuscany metropolitan area network (MAN), while St-Luc University Hospital was connected to Belgium ATM network through the Brussels MAN. By means of international connections provided by the European JAMES project, a link between the two sites was established, connecting both national ATM networks. Due to the large variety of hardware present in the medical centers, multiplatform software tools were used and tested: central test node (CTN) release 2.8, VAT, NV-3.3, and IDI (UCL homemade multiplatform teleradiology tool for interactive visualization and processing of DICOM images).